Clinical Echocardiography and Other Imaging Techniques in Cardiomyopathies - Pinamonti, Bruno; Sinagra, Gianfranco (New York Springer, 2014)
The Book consists of 5 part:1-Cardiomyopathies. 2- Dilated Cardiomyopathy. 3-Hypertrophic Cardiomyopathy. 4-Arrhythmogenic Right Ventricular Cardiomyopathy. 5-Restrictive,Infiltrative/storage and other Cardiomyopathies
Includes references p. p. 272:280
3
Keywords: Cardiomyopathies; Echocardiography